Respuesta :
Answer:
[tex]P(A|B)=\frac{40}{49}[/tex]
Step-by-step explanation:
We know that
the general equation for conditional probability is
[tex]P(A|B)=\frac{P(AnB)}{P(B)}[/tex]
we are given
[tex]P(AnB)=\frac{5}{7}[/tex]
[tex]P(B)=\frac{7}{8}[/tex]
now, we can plug values
[tex]P(A|B)=\frac{\frac{5}{7}}{\frac{7}{8}}[/tex]
now, we can simplify it
[tex]P(A|B)=\frac{5\cdot \:8}{7\cdot \:7}[/tex]
so, we get
[tex]P(A|B)=\frac{40}{49}[/tex]
Answer:
[tex]\frac{40}{49}[/tex]
Step-by-step explanation:
We are given the probabilities P(A∩B)=5/7 and P(B)=7/8 and we are to find P(A|B) according to the general equation for conditional probability.
So we will use the following formula for this:
P(A|B) = P(A∩B) / P(B)
Substituting the given values in the above formula to get:
P(A|B) = [tex]\frac{\frac{5}{7} }{\frac{7}{8} }[/tex] = [tex]\frac{5}{7} * \frac{8}{7}[/tex]
P(A|B) = [tex]\frac{40}{49}[/tex]